Radical Gotham : Anarchism in New York City from Schwab's Saloon to Occupy Wall Street - Goyens, Tom, 1972- (Book collections on Project MUSE., 2017)
"A collection of scholarly essays focused on a sophisticated and historical examination of the anarchist traditions in politics, publishing, the arts, economic justice, and economic identity in New York City over the last 150 years. Tom Goyens argues that New York's identity as a cultural and artistic center, as a point of arrival for millions of immigrants, and as a hub of capitalism makes the city a unique and influential terrain for the study of anarchism, with special attention to how anarchism is situated physically, politically, and culturally in New York City. The collection includes essays on German, Italian, and Yiddish- and Spanish-speaking anarchists as well as anarchism in relation to religion, politics, and art. The collection culminates in an essay on how the Occupy Wall Street movement's general assemblies, decision making by hand signals, and alternative uses of space and resources demonstrate anarchist tendencies rooted in the immigrant radical communities of New York City"--